Frequency of Subfertility in Women with High Body Mass Index (BMI) - Daudpota, Sofia; Shah, Nighat; Aftab, Syeda Aliza; Daudpota, Rahid Ali; Irum, Sobia (Indus Journal of Bioscience Research, 2025)
Objectives: It is essential to carry out a study to ascertain the prevalence of subfertility in women with high BMI because of these inconsistent results and the dearth of data in the local population. The findings of this study will assist us in providing evidence-based education to women with high BMI and subfertility about the advantages of weight loss for increased fertility. Study Design: Descriptive, cross-sectional study. Settings: Department of Obstetrics & Gynecology, Jinnah Postgraduate Medical Centre, Karachi. Duration of study: November 2022 to April 2023. Methodology: A total of 138 women of reproductive age, aged 15 to 45, with a high BMI (≥ 25 kg/m2) were chosen. Individuals with low or normal body mass index, a history of pregnancy, thyroid and androgen hormone endocrine abnormalities, and the use of any form of contraception were not included. The researcher recorded baseline information such as age, height, weight, BMI, and menstrual cycle regularity. A consultant gynecologist evaluated each patient in the trial for subfertility, which was defined as the inability to conceive after a year of unprotected sexual activity. Results: The study’s participants ranged in age from 15 to 45, with a mean age of 26.54 ± 5.93 years. A mean height of 159.12 ± 12.65 cm was recorded. 79.87 ± 8.71 kg was the average weight. Mean BMI was 33.24 ± 6.52 kg/m2. 55 individuals (39.86%) with high BMI had subfertility. Conclusion: Obesity and overweight are prevalent disorders that have an impact on reproductive health in addition to overall health.